PRINCIPAL'S CLINICAL SUPERVISION: TEACHERS' PERSPECTIVES ON INSTRUCTIONAL FEEDBACK - Bachtiar Hariyadi; Ahmad Hariyadi; Agus Setyawanto (Universitas Nahdlatul Ulama Pasuruan, 2024)
The purpose of this study was to investigate the instructional feedback given by Principals during classroom observations. A qualitative approach was used, with semi-structured interviews conducted to gather data. Content analysis was employed to analyze the data. The participants were 20 elementary school teachers from Surabaya city in the 2023-2024 academic year, selected through purposive sampling. The findings revealed that Principals showed insufficient competence in supervision, conducting classroom observations only once a year as a formal procedure. Compared to educational supervisors, Principals were found to need greater proficiency in managing instructional issues faced by teachers due to their familiarity with teachers and knowledge of school activities. The study highlighted that teachers did not find the feedback provided by Principals beneficial, as it was seen as general advice. Therefore, it is essential for administrators to learn effective supervision methods to support instructional improvements in schools. Principals should understand how their role in the supervision system impacts the feedback they provide to teachers.